The Development Of 8-Inch Roll-To-Plate Nanoimprint Lithography(8-R2p-Nil) System With Uv-Led Exposure - Lee, Lai Seng (2019)
Lithography, a significant tool in microchip manufacturing experiences major changes in lens material and design due to reduction of radiation wavelength used in conventional lithography tool. This is caused by shrinkage of microchip size in accordance to Moore's law over the years. This paves way to the development of unconventional nanofabrication techniques with nanoimprint lithography is accepted as the most promising candidate. There are a few limitations in Thermal-Nanoimprint Lithography (Thermal-NIL). Thermal cycle and thermal mismatch causes low imprint throughput and building up of stress in substrate and imprint mold respectively. Besides, heating of thermoplastic film also contributes to high electricity consumption. In addition, large surface contact area between hard flat mold and resist in Thermal-NIL causes high imprint force and large demolding force. Furthermore, surface waviness of substrate and hard flat mold hinders conformal contact during imprinting. Apart from that, air traps in between resist and hard flat mold causes void defects. Therefore, in this work a prototype for 8-Inch Roll-To-Plate Nanoimprint Lithography system has been developed to overcome the limitations of Thermal-NIL. Quartz tube was employed as imprint roller to imprint patterns on silicon wafer. UV-LED was selected as UV curing source to cure SU-8 2002 photoresist. PDMS flexible molds were fabricated and were attached to quartz tube imprint roller to imprint patterns onto silicon wafer. Prior to imprinting process, a SU-8 2002 spun coated silicon wafer was placed onto vacuum chuck and was moved forward passing underneath a rotating imprint quartz tube. In the meantime, imprinted patterns on silicon wafer was cured by UV-LED. Shortly after curing, PDMS flexible mold was detached from imprinted structures in a 'line peeling' pattern. Experimental works were started with the fabrication of SU-8 2002 master molds and replication of PDMS flexible molds. With 1.00 mm/s of imprint linear speed, UV intensity of 2700 μW / cm2 was identified to be the most optimum level to provide sufficient UV dose for SU-8 2002 photoresist curing. The almost instant curing of SU-8 2002 photoresist by UV-LED greatly increases imprint throughput. Moreover, room temperature imprinting was achieved by using UV-LED as SU-8 2002 photoresist curing source. Result from imprint speed experimental work indicates that average imprint depth decreases from 1.04 μm to 0.73 μm with increases in imprint speed from 0.2 mm/s to 4.0 mm/s. Furthermore, increase in imprint force from 10.00 N to 14.00 N was observed to improve average imprint depth from 0.97 μm to 2.11 μm. Findings from experimental works suggests that the proposed 8-Inch Roll-To-Plate Nanoimprint Lithography system prototype effectively performs room temperature imprinting with UV-LED as resist curing source. In addition, the proposed method of fabricating PDMS flexible mold is an effective way to fabricate flexible mold. It is to my knowledge from literature, little effort being put into research of using UV-LED as resist curing source, micro heat pipe and copper heat pipe as heat dissipation elements. Moreover, little effort has been done to install UV-LED together with heat dissipation elements inside quartz tube imprint roller for R2P-NIL.